Flow dynamic assessment of native mitral valve, mitral valve repair and mitral valve replacement using vector flow mapping intracardiac flow dynamic in mitral valve regurgitation - Pugliese, Nicola Riccardo; Colli, Andrea; Falcetta, Giosuè; Del Punta, Lavinia; Puccinelli, Carlo; Fiocco, Alessandro; Petronio, Anna Sonia; Taddei, Stefano; Masi, Stefano; Besola, Laura (Frontiers in Cardiovascular Medicine, 2023)
Objectives:The present study aims to assess and describe the intracardiac blood flow dynamic in patients with mitral regurgitation (MR), repaired mitral valves and mitral valve prostheses using vector flow mapping (VFM). Methods: Patients with different MV pathologies and MV disease treatments were analysed. All patients underwent 2D transthoracic echocardiography, and images for flow visualization were acquired in VFM mode in an apical three-chamber view and four-chamber view. Vectors and vortices were qualitatively analyzed. Results: thirty-two (32) patients underwent 2D transthoracic echocardiography (TTE) with VFM analysis. We evaluated intracardiac flow dynamics in 3 healthy subjects, 10 patients with MR (5 degenerative, 5 functional), 4 patients who underwent MV repair, 5 who underwent MV replacement (3 biological, 2 mechanical), 2 surgically implanted transcatheter heart valve (THV), 2 transcatheter edge-to-edge MV repair with MitraClip (TEER), 3 transcatheter MV replacement (TMVR) and 3 transapical off-pump MV repair with NeoChord implantation. Blood flow patterns are significantly altered in patients with MV disease and MV repaircompared to control patients. MV repair is superior to replacement in restoring more physiological patterns, while TMVR reproduces an intraventricular flow closer to normal than surgical MVR and TEER. Conclusions: Intracardiac flow patterns can be clearly defined using VFM. Restoration of a physiological blood flow pattern inside the LV directly depends on the procedure used to address MV disease.